Rom, Italien. Kollektive Bestattungen in Rom zwischen später Republik und Spätantike. Forschungsüberblick der Jahre 2016 bis 2018 - Zimmermann, Norbert; Fröhlich, Thomas; Haps, Silke; Mayer, Irmengard; Felle, Antonio E.; Vilello, Antonello (e-Forschungsberichte des DAI, 2019)
In 2016, the department Rome of the German Archaeological Institute startet the project „New research on collective burial spaces in Rome from the Late Republican to Late Roman period “. This report gives an overview on the activities undertaken so far and aims to provide some exemplary insights to the results. The research is based directly on the findings which were made during the DAI-project on the colombarium of Scribonius Menophilus (Th. Fröhlich – S. Haps) and the START-project on the catacomb of Domitilla (N. Zimmermann, until 2014 with the Institute for the Study of Ancient Culture, Austrian Academy of Science).